FAKTOR – FAKTOR YANG MEMPENGARUHI KINERJA UMKM DIMODERASI OLEH KETIDAKPASTIAN LINGKUNGAN ( Studi Empiris Pada UMKM Krcamatan Sukajadi Kota Pekanbaru ) - Aprilianti Aprilianti; Kamaliah Kamaliah; Aunurrafiq Aunurrafiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of accounting information systems, financial literacy and human resources competencies on the performance of micro, small and medium enterprises with environmental uncertainty as a moderating variable. The data used in this study are primary data, with a questionnaire as an instrument. The method used for sample selection was purposive sampling. In this study, the total of UMKM in Sukajadi District was 295 UMKM. The research sample was 170 UMKM. But only 150 answered the questionnaire and it can be processed. The data analysis technique used in this study is multiple linear regression analysis and moderated regression analysis using Statistical Product and Service Solution (SPSS) data processing software version 20.0 for windows. The results showed that the accounting information system, financial literacy and human resources competencies had an effect on the performance of micro, small and medium enterprises. Moderated regression analysis shows that environmental uncertainty can moderate and strengthen the influence of accounting information systems, financial literacy and human resources competencies on the performance of micro, small and medium enterprises.Keywords: Accounting Information System, Financial Literacy, Human Resources Competencies, Environmental Uncertainty and The Performance of micro, small and medium enterprises